2022
DOI: 10.3390/ijms23010538
|View full text |Cite
|
Sign up to set email alerts
|

Bisdemethoxycurcumin Induces Cell Apoptosis and Inhibits Human Brain Glioblastoma GBM 8401/Luc2 Cell Xenograft Tumor in Subcutaneous Nude Mice In Vivo

Abstract: Bisdemethoxycurcumin (BDMC) has biological activities, including anticancer effects in vitro; however, its anticancer effects in human glioblastoma (GBM) cells have not been examined yet. This study aimed to evaluate the tumor inhibitory effect and molecular mechanism of BDMC on human GBM 8401/luc2 cells in vitro and in vivo. In vitro studies have shown that BDMC significantly reduced cell viability and induced cell apoptosis in GBM 8401/luc2 cells. Furthermore, BDMC induced apoptosis via inhibited Bcl-2 (anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…It enhances α -PD-L1 antibody-mediated immune responses against bladder cancer [ 39 ]. It induces glioblastoma cell apoptosis [ 40 ]. Besides, it could cause a decrease in HCC cell viability and an increase in apoptosis [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It enhances α -PD-L1 antibody-mediated immune responses against bladder cancer [ 39 ]. It induces glioblastoma cell apoptosis [ 40 ]. Besides, it could cause a decrease in HCC cell viability and an increase in apoptosis [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…BDMC comprises approximately 3% of curcuminoids and is more stable than others in vivo [ 131 ]. Recent studies have suggested that BDMC plays an antitumor role via multiple biological mechanisms or synergistic modes of action, from the suppression of cell growth, proliferation, invasion, and migration, to the induction of programmed cell death in various cancers [ 132 , 133 , 134 , 135 , 136 , 137 ].…”
Section: The Impact Of Cur Analogs On Nsclcmentioning
confidence: 99%
“…Glioblastoma (GBM) is an aggressive type of glioma associated with resistance to treatments and recurrence; patients with GBM usually have a short survival rate ( 4 ). It is responsible for 50%-60% of all brain tumors and 12%-15% of all intracranial tumors ( 5 , 6 ). About 75% of temozolomide (TMZ) treated GBM patients die within 2 years owing to recurrence, demonstrating that GBM patient survival rates remain dismally poor ( 7 ).…”
Section: Introductionmentioning
confidence: 99%